2005
DOI: 10.1007/s10853-005-1983-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of transient liquid phase bonding and other diffusion controlled phase changes

Abstract: Diffusion in material of inhomogeneous composition can induce phase changes, even at a constant temperature. A transient liquid phase (TLP), in which a liquid layer is formed and subsequently solidifies, is one example of such an isothermal phase change. This phenomenon is exploited industrially in TLP bonding and sintering processes. Successful processing requires an understanding of the behaviour of the transient liquid layer in terms of both diffusion-controlled phase boundary migration and capillarity-driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 13 publications
4
30
0
Order By: Relevance
“…However, none of the proposed improvements actually render the algorithms conservative of solute. The authors of the present work have previously shown that conservative schemes can be derived by adopting a different approach to modelling the interfacial fluxes [31].…”
Section: Numerical Solution Techniquesmentioning
confidence: 92%
“…However, none of the proposed improvements actually render the algorithms conservative of solute. The authors of the present work have previously shown that conservative schemes can be derived by adopting a different approach to modelling the interfacial fluxes [31].…”
Section: Numerical Solution Techniquesmentioning
confidence: 92%
“…Once the liquid has become homogeneous, solidification takes place at a rate determined by the rate of diffusion within the solid phase. This assumption is supported by numerical simulations [4,6,20].…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 62%
“…The present authors recently published [16,20] an algorithm designed to obtain approximate solutions to Eqs. (1)- (6), to any required accuracy.…”
Section: Numerical Solutionsmentioning
confidence: 99%
“…The discretization points are defined by a fixed discretization of , , and they may be written as , . The finite volume discretization [8] of (11) is based on integration around the nodes and is fairly straightforward [9], [10]. The boundary conditions (8) and (10) The finite volume discretization for (12) and (13) immediately follows from the general form of the finite volume integral.…”
Section: A Front-fixing Methodsmentioning
confidence: 99%